الأبعاد الإسلامية في روايات غرب أفريقيا الفرنكوفونية : دراسة تحليلية - بمبا، آدم (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
This study which is entitled "The Islamic Dimensions in West African Francophone Novels: Analytical Study", examined a considerable number of West African Francophone novels published between 1930 and 2000 with special reference to Muslim novelists. The main objective is to explore the Islamic dimensions of their works. The researcher adopted the Social Method in literary studies based on the Generative-Structural method that was elaborated by the French critic Lucien Goldmann. This is commonly known as the theory of "Vision du Monde" (world-View), which embodies both the structure and the social content of the literary text. Analyzing novels according to their various elements in terms of personage, time, place and event, the study found that the Islamic influence is relatively obvious in various structural elements of the analyzed novels. From this point, there emerges the value of Islam as a core element in shaping the "World-View" of novelists in the African Muslim society in general and in West Africa in particular. This World-View is clearly manifested in subjects like the critic of the society, the belief in Allah, Islamic fundamental pillars and Sufism. It has also been well presented by renowned novelists such as Ahmadou Kourouma, Amadou Hampate Ba, Aminata Sow Fall, Camara Laye, Hamidou Kane, Mariama Ba, Mariama N'Doye and Massa Makan Diabate. The Islamic World-View has also affected the linguistic changes in the novels starting from the Islamic words to the frequent quotations from various Islamic sources and references. Therefore, this study supplements previous studies of Islamic influence on various African social and cultural aspects. On the basis of the fundamental findings in this study, it can be concluded that literature in general and the art of the novel in particular are more capable in absorbing and reflecting Islamic values of human life and culture.